2016
DOI: 10.2350/16-03-1789-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Placental Pathologic Associations with Morbidly Adherent Placenta: Potential insights into Pathogenesis

Abstract: MAP is highly associated with evidence of intraparenchymal placental hemorrhage villous changes of MVU, and a lymphoplasmacytic infiltrate at the implantation site. The contribution of this basal chronic inflammatory infiltrate to MAP requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 0 publications
0
45
1
3
Order By: Relevance
“…(27) Additionally, the panel felt that evidence for other features commonly seen in the setting of accreta was not sufficient for use as the sole criterion for diagnosis. Most cases of PAS will show overlapping features of tissue injury with degenerated or shriveled myofibers, interstitial edema and chronic inflammation, (2,28,29) [https://slide-atlas.org/link/opzzzv] 3. PAS with more extensive tissue destruction.…”
Section: Gross Featuresmentioning
confidence: 99%
“…(27) Additionally, the panel felt that evidence for other features commonly seen in the setting of accreta was not sufficient for use as the sole criterion for diagnosis. Most cases of PAS will show overlapping features of tissue injury with degenerated or shriveled myofibers, interstitial edema and chronic inflammation, (2,28,29) [https://slide-atlas.org/link/opzzzv] 3. PAS with more extensive tissue destruction.…”
Section: Gross Featuresmentioning
confidence: 99%
“…The significance of leukocyte subpopulations and their contribution to excessive invasion of extravillous trophoblasts (EVT) in PAS requires further investigation; however, initial studies are intriguing. Ernst et al demonstrated an increased lymphocytic infiltrate at the implantation site in a series of 101 PAS specimens compared to patients with placentas sent for examination due to a history of maternal malignancy with no clinical suspicion of PAS [ 32 ].…”
Section: Molecular Biologymentioning
confidence: 99%
“…Other histological findings which were significantly more frequently seen in morbidly adherent placentas when compared to controls include basal chronic villitis, chronic lymphoplasmacytic inflammation in the basal plate, villous agglutination, remote retromembranous hemorrhage, subchorionic intervillous thrombi , and chorionic villi extending into myometrial vascular spaces in postpartum hysterectomies. Morbidly adherent placenta is a frequent cause of postpartum hemorrhage, delayed separation or retained placenta, which is defined clinically as placenta expulsion at least 30 minutes after the delivery of the newborn .…”
Section: Types Of Abnormal Placentationmentioning
confidence: 98%